Socio-spatial segregation in the spread and lethality of the COVID-19 in the city of Lima 2020-2021 - Ticona Fernández Dávila, Rubén (2021)
This research studies exploratorily the relationship between socio-spatial segregation in the spread of the COVID-19 disease and its lethality in the city of Lima. The consequences of the COVID-19 pandemic have revealed the inconsistencies of an uncontrolled urban growth in different Peruvian cities as well as inequalities within them, boosting the devastating effects of the pandemic, what placed Peru at the top of the list of the countries with the highest lethality in the world from COVID -19. In this regard, it is considered the urban-socio spatial segregation as the spread and amplifying cause of the COVID-19, especially in popular sectors. Methodologically, the research is based on the exploratory method using a mixed methodology bibliographic review, field observation and quantitative data to approach the effects of the pandemic and the unequal impact in Lima city.